Perspectives for women's empowerment through the reading of children's classics for initial educational series - Figueredo, Sandriane Proença (2020)
This article discusses the issue of women's empowerment and aims to reflect on a pedagogical proposal for primary school students in a public school in the municipality of São Gabriel/RS. Students from the fifth year of elementary school. The objective was to report a reflection on the role of women in contemporary society, starting from a rereading of children's classics. It is considered that by discussing new teaching and learning practices related to the role of women in the contemporary world, we can stimulate educators to seek new perspectives for their practices in all areas of knowledge. The result of these practices after analyzing the students' reports was to raise everyone's awareness about the importance of women's struggle and achievements in contemporary society. It was considered that "contemporary princesses" can save themselves and achieve the expected "happy ending" that most fairy tales bring, without, however, counting on a "prince charming". In this context it was realized that women's achievements are part of a modern reality, which must always be related to all teaching practices.